Feasibility of progressive polyp contraction with underwater endoscopic mucosal resection in ≥ 20 mm superficial colorectal lesions - Okada, Masahiro; Shinozaki, Satoshi; Nomura, Tatsuma; Hayashi, Yoshikazu; Morikawa, Takaaki; Kitamura, Masafumi; Fukuda, Hisashi; Arita, Munefumi; Takezawa, Takahito; Sunada, Keijiro; Lefor, Alan Kawarai; Yamamoto, Hironori (Endoscopy International Open, 2022)
Background and study aims Underwater endoscopic mucosal resection (UEMR) does not always result in en bloc resection of large colorectal lesions. The aim of this study was to demonstrate the feasibility of en bloc resection with progressive polyp contraction with underwater endoscopic mucosal resection (PP-CUE) of large, superficial colorectal lesions. The advantage of PP-CUE is to enable resection of a superficial non-polypoid lesion that is larger than the snare diameter.Patients and methods Eleven consecutive lesions in ten patients who underwent UEMR with PP-CUE of large superficial colorectal lesions (20 mm or greater) were included.Results The median lesion diameter was 24 mm (interquartile range [IQR], 20–24 mm). All lesions were larger than the 15-mm rotatable snare that was used. Median procedure time and PP-CUE time were 11 minutes (IQR, 8.5–12.3) and 2.3 minutes (IQR, 1.9–3.4), respectively. Pathological diagnoses of resected specimens included six adenomas, three sessile serrated lesions, and two slightly invasive submucosal carcinomas. En bloc and R0 resection rates were both 91 % (10/11). No adverse events occurred.Conclusions PP-CUE is useful to resect superficial non-polypoid colorectal lesions 20 to 25 mm in diameter in an en bloc fashion.